First record of the genus Augilina Melichar, 1914 (Hemiptera, Fulgoromorpha, Caliscelidae) from China, with descriptions of two new bamboo-feeding species - Gong, Nian; Yang, Lin; Chen, Xiang-Sheng (European Journal of Taxonomy, 2021)
The planthopper genus Augilina Melichar, 1914, is recorded in China for the first time. Two new species of the genus Augilina, A. tetraina Chen & Gong sp. nov. and A. triaina Chen & Gong sp. nov., are described and illustrated from South China. The genus now has a total of four described species. New generic characteristics are proposed and photographs of the new species are provided. A checklist and a key to the species of Augilina are also included.